Pengaruh Kompetensi dan Pelatihan Guru Terhadap Hasil Belajar Siswa Kelas IX TP. 2015/2016 di SMP Swasta Yayasan Perguruan Nasional Etislandia Medan - R.L. Holmes Parhusip (Universitas Quality, 2017)
Competence is the ability to implement something that is is obtained through education and training. The training is an activity of a company that intends in order to improve and develop the attitudes, behaviors, skills and knowledge of employees in accordance with the desire from the companies concerned. The results study of are a reflection of the success of of students in participating the process of learning that followed.The population in this research is the whole a teacher at the National Junior College Foundation Private Etislandia Medan, with large samples taken of 50 people. Validity of test results as a test run for the variables X1, X2, and Y be seen that the whole grain questionnaire items is valid, so the whole grain questionnaire items variables X1, X2, and Y in the study actually no one autumn. The results of the reliability test on a trial for the variables X1, X2, and Y appears that constructs question variable factors X1, X2, and Y is very relibel. Based on the results of a frequency distribution known that the tendency of the respondents in answer to of questionnaires for the variables X1 is High, for variable X2 is Extremely High, and to the variable Y is Quite / Medium.